Settler Colonialism A Theoretical Overview - Veracini, L. (Cambridge Imperial and Post-Colonial Studies Series, 2010)
A vivid exploration of the history of a very powerful and long lasting idea: building European worlds outside of Europe. Veracini outlines how the founding of new societies was envisaged and practiced and explores the specific ways in which settler colonial projects tried to establish ideal and regenerated political bodies.